Elements for the analysis of the interaction of learning between the different agents intervening in the Practicum of Physiotherapy - Yolanda Sánchez; Marina Tomàs-Folch (Universitat Politècnica de València, 2019)
This Practicum constitutes an essential element in the training process of physiotherapy students prompted by the need to connect its theoretical and practical parts. Both the external and internal activities ought to be balanced in teaching as those are considererd to be key factors for active learning throughout the formation process. During the attendance phase of the internship, the students will need to be able to act professionally by identifying and solving any type of problems supported by their internship adviser both using the knowledge adquired in the course and the argumentations conducted in the University lectures. In this journal we present a first phase of a research whihch is aimed at finding out the elements for the analysis of the interactions of learning between the agents intervening in the subect areas included in Practicum I, II and Practicum V, VI. We have chosen a qualitative metholdology of etnographic design. A focus group has been carried out, being composed by experts in the theoretical and practical fields who comment on and discuss about the intervening elements starting from different questions formulated. The elements for the analysis of the learning interactions between the intervening agents in Practicum I, II and Practicum V, VI can be grouped in the following categories: organisation, coordination, relation between the intervening elements, functions, and achievements of the learning process and evaluation.